Predicting lymph node metastasis in pT1 colorectal cancer: a systematic review of risk factors providing rationale for therapy decisions - Bosch, Steven L.; Teerenstra, Steven; de Wilt, Johannes H. W.; Cunningham, Chris; Nagtegaal, Iris D. (Endoscopy, 2013)
Background and study aim: Population screening for colorectal cancer (CRC) is expected to increase the number of pT1 CRCs. Local excision is an attractive treatment option, but is only oncologically safe in the absence of lymph node metastasis (LNM). A systematic review of the predictive value of pathological risk factors for LNM in pT1 CRC was conducted to provide data for an evidence-based decision regarding follow-up or radical surgery after local excision.Methods: PubMed was searched for reports on predictors of LNM in pT1 CRC. Published papers written in English and containing at least 50 patients were included. Meta-analyses were performed using Review Manager 5.1. Results: A total of 17 studies were included involving a total of 3621 patients with available nodal status. The strongest independent predictors of LNM were lymphatic invasion (relative risk [RR] 5.2, 95 % confidence interval [CI] 4.0 – 6.8), submucosal invasion ≥ 1 mm (RR 5.2, 95 %CI 1.8 – 15.4), budding (RR 5.1, 95 %CI 3.6 – 7.3), and poor histological differentiation (RR 4.8, 95 %CI 3.3 – 6.9). Limitations of the study were: results could not be stratified according to location in the colon or rectum; very early tumors removed by polypectomy without surgical resection were not included in the meta-analysis; and included studies were primarily from Asian countries and results therefore need to be verified in Western populations.Conclusion: The absence of lymphatic invasion, budding, submucosal invasion ≥ 1 mm, and poor histological differentiation were each associated with low risk of LNM. Risk stratification models integrating these factors need to be investigated further.